Ethanol extract of Cymbopogon winterianus on mortality and number of eggs of Tetranychus urticae - Victor Bernardo Vicentini; Dirceu Pratissoli; Vagner Tebaldi de Queiroz; Adilson Vidal Costa; Patrícia Fontes Pinheiro; Fernando Domingo Zinger; Vando Miossi Rondelli (Ciência Rural, 2015)
Plant extracts have been studied as a promising source of natural insecticides. This study assessed the effect of the ethanol extract of Cymbopogon winterianus Jowitt (citronella grass) in comparison with an insecticide containing azadirachtin (ICA) on mortality and number of eggs of Tetranychus urticae Koch (Acari: Tetranychidae) in laboratory conditions. For the tests, the mites were sprayed with the aid of a Potter spray tower. To assess the mortality of females, LC50 value for extract of citronella grass and ICA was, respectively, 2.63 and 2.83%. With respect to the number of eggs, the greatest reduction was observed at a concentration of 5% for the evaluation period of 120h, both for the extract of citronella grass (86%) and for ICA (81%). These results suggest the potential of the ethanol extract of citronella grass to control of T. urticae. However, experiments, under field conditions, involving other populations of T. urticae should be performed to verify the efficacy of this extract as an alternative to be used in pest management programs